2018
DOI: 10.4103/ijpvm.ijpvm_403_16
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for addiction potential among college students

Abstract: Background:Tendency toward addiction is provided before drug use begins. The present study aimed to identify the risk factors for addiction potential in the students of Arak University of Medical Sciences.Methods:We conducted this cross-sectional study among 305 students from Arak University of Medical Sciences, Iran in 2016. We selected the students by stratified random sampling and collected the data by family and sociodemographic factors questionnaires and Addiction Potential Scale.Results:Male students, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
3
4
2
Order By: Relevance
“…In some studies, the mean score of addiction potential was higher than the results of this study, which is inconsistent with our results [5,31,[34][35][36]. The results of this study are consistent with the low mean score of addiction potential reported in other studies [3,4,9,22,43]. Perhaps one of the reasons for the discrepancy is the study environments and types of university.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In some studies, the mean score of addiction potential was higher than the results of this study, which is inconsistent with our results [5,31,[34][35][36]. The results of this study are consistent with the low mean score of addiction potential reported in other studies [3,4,9,22,43]. Perhaps one of the reasons for the discrepancy is the study environments and types of university.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the score of addiction potential was lower among women, there was no significant relationship between addiction potential and gender. A number of studies reported a significant relationship between sex and addiction potential which is inconsistent with the present results [22,31,35,45].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This causes them to have more addictive behaviors to escape the unpleasant feelings they experience through suppressing their anger. However, results of Baron-Oladi et al [25] and Ranjbaran et al [26] are against this claim. Baron-Oladi et al reported that male preuniversity students in Kerman were more prone to addiction than female students, and in the study of Ranjbaran et al , male students of Arak University of Medical Sciences reported higher potential for addiction.…”
Section: Discussionmentioning
confidence: 97%